2021
DOI: 10.1007/s40519-021-01157-w
|View full text |Cite
|
Sign up to set email alerts
|

The #orthorexia community on Instagram

Abstract: Purpose This mixed-methods study delved into the relationship between orthorexia nervosa (ON) and Instagram. Methods Two quantitative data sources were used: content analysis of pictures using #orthorexia (n = 3027), and an online questionnaire investigating the experience of ON and the use of Instagram of people sharing ON-related content on Instagram (n = 185). Following, interviews (n = 9) were conducted with people posting ON-related content on Instagr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…However, as noted by Valente et al [ 24 ], research that engages with lived experiences can provide vital experiential knowledge to develop clinical understandings of and approaches to ON. Consistent with this, researchers have examined discussions of ON by analysing the hashtag ‘#Orthorexia’, finding that Instagram encourages problem realisation and a sense of belonging through this hashtag [ 25 ]. In an analysis of this hashtag, Santarossa et al [ 23 ] found that the ON Instagram community is a relatively small but supportive community which focuses on recovery and adopting healthier eating behaviours.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, as noted by Valente et al [ 24 ], research that engages with lived experiences can provide vital experiential knowledge to develop clinical understandings of and approaches to ON. Consistent with this, researchers have examined discussions of ON by analysing the hashtag ‘#Orthorexia’, finding that Instagram encourages problem realisation and a sense of belonging through this hashtag [ 25 ]. In an analysis of this hashtag, Santarossa et al [ 23 ] found that the ON Instagram community is a relatively small but supportive community which focuses on recovery and adopting healthier eating behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…While some of these researchers have included recovery hashtags (i.e. #OrthorexiaRecovery) in their data collection strategies [ 24 , 25 ], internet-mediated research that specifically focuses on recovery is limited [ 10 ]. We address this gap in the literature, building upon the work of Valente et al [ 24 , 25 ] and Ross Arguedas [ 10 ] to examine narratives of recovery under the hashtag ‘#OrthorexiaRecovery’.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that Instagram was associated with higher ON (Turner & Lefevre, 2017). People who shared content that indicated ON were more likely to heavily use social media; specifically, Instagram was shown to heavily promote ON (Valente et al, 2021). Instagram is a relatively new social media platform that was created in 2010 where users can publish updates in the form of photos (Hu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%